Ambient Temperature During Gestation and Cold-Related Adult Mortality in a Swedish Cohort, 1915 to 2002 - Tim A. Bruckner; Gerard J. van den Berg; Kirk R. Smith; Ralph A. Catalano (Institute for the Study of Labor (IZA), 2014)
For all climatic regions, mortality due to cold exceeds mortality due to heat. We examine whether cold-related mortality in adulthood varies positively with unusually benign ambient temperature during gestation, using data on over 13,500 Swedes from the Uppsala Birth Cohort Study born in 1915-1929 and followed until 2003. We link daily thermometer temperatures in Uppsala (1914 to 2002) to subjects, from their estimated date of conception onwards. We estimate survival models with time-varying explanatory variables, focusing on the two leading causes of cold-related death in adulthood: ischaemic heart disease (IHD) and stroke. An increase in the prevalence of warm temperatures during gestation leads to a significantly higher rate of mortality due to cold-related IHD. However, we do not find such a relation for cold-related stroke mortality. Additional analyses show that birthweight percentile or gestational age do not mediate discovered findings. The IHD results indicate that ambient temperature during gestation independent of birth month modifies the relation between cold and adult mortality.
Keywords: I12; Q54; 330; temperature regulation; climate; cerebrovascular disorders; cold spells; fetal development; health; ischaemic heart disease; migration